Sintilimab plus Lenvatinib conversion therapy for intermediate/locally advanced hepatocellular carcinoma: A phase 2 study - Wang, Lijun; Wang, Hongwei; Cui, Yong; Liu, Ming; Jin, Kemin; Xu, Da; Wang, Kun; Xing, Baocai (Frontiers in Oncology, 2023)
Abstract Introduction Patients with intermediate or locally advanced hepatocellular carcinoma (HCC) who are not eligible for radical treatment typically have a poor overall prognosis. Treatment strategies that can convert unresectable HCC into resectable HCC may improve patient survival. We conducted a single arm phase 2 trial to evaluate the efficacy and safety of Sintilimab plus Lenvatinib as conversion therapy for HCC. Methods A single-arm, single-center study conducted in China (NCT04042805). Adults (≥18 years) with Barcelona Clinic Liver Cancer (BCLC) Stage B or C HCC ineligible for radical surgery with no distant/lymph node metastasis received Sintilimab 200 mg IV on day 1 of a 21-day cycle plus Lenvatinib 12 mg (body weight ≥60 kg) or 8 mg (body weight <60 kg) orally once daily. Resectability was based on imaging and liver function. The primary endpoint was objective response rate (ORR), assessed using RECIST v1.1. Secondary endpoints included disease control rate (DCR), progression-free survival (PFS), event-free survival (EFS) in patients who underwent resection, surgical conversion rate, and safety. Results Overall, 36 patients were treated between August 1, 2018, and November 25, 2021; the median age was 58 years (range, 30–79), and 86% were male. The ORR (RECIST v1.1) was 36.1% (95% CI, 20.4–51.8) and the DCR was 94.4% (95% CI, 86.9–99.9). Eleven patients underwent radical surgery and one received radiofrequency ablation and stereotactic body radiotherapy; after a median follow up of 15.9 months, all 12 were alive and four had recurrence, median EFS was not reached. Median PFS among 24 patients who did not undergo surgery was 14.3 months (95% CI, 6.3–26.5). Treatment was generally well tolerated; two patients had serious adverse events; there were no treatment-related deaths. Conclusions Sintilimab plus Lenvatinib is safe and feasible for the conversion treatment of intermediate to locally advanced HCC initially unsuitable for surgical resection.